THE DEVELOPMENT OF STUDENTS’ THINKING USING COLORED CARDS TOWARDS INTERSECTION AND UNION CONCEPT - Mika Meitriana Manurung; Hening Windria; Lukman Fakhmi (Universitas Lambung Mangkurat, 2017)
Intersection and union concepts are crucial part of operation in sets, especially in solving word problems and creating the venn diagram. In fact, not a few students do fallacies in representing sets word problems into a sets operation, so they do mistakes in solving the problems. This study aims to investigate students’ thinking in learning intersection and union concept, specifically by using colored cards. The learning is designed under Realistic Mathematics Education (RME) approach and the principle used is emergent modeling. The method used in this study is design research. The subjects of this study is 25 students of the 7th grade junior high school, in which five of them were the focused group. The main findings in this study are description of students’ thinking while learning union and intersection using colored cards in the class, and any kinds of students’ ‘diagram venn’models. Keywords: design research, intersection, realistic mathematics education, union, venn diagram